EFEKTIVITAS PENERAPAN MODEL KOOPERATIF TIPE NHT DENGAN PENDEKATAN AUDITORY INTELLECTUALLY REPETITION DALAM PEMBELAJARAN MATEMATIKA - Hasma Mallaherang; Nurdin Arsyad; Muhammad Darwis (Vidya Karya, 2018)
Abstract. This research aims to describe the effectivity of cooperative learning model from the type of Numbered Head Together (NHT) with the Auditory Intellectually Repetition (AIR) Approachment in mathematics instruction. Type of research is a pre-experiment. Population of the research is all of the tenth grade (class X) students of public senior high school (SMAN) 2 Bua Ponrang. The research sample was students of class X-1 selected through random sampling techniques. Research data were collected by using test and observation techniques. The results showed that (a) Cooperative learning model from NHT type with AIR approachment instruction has been well implemented, (b) students’ activity was in ideal category, (c) students' responses toward the instruction was tend to be positive, and (d) student’s achievements was classically mastered with normalized gain was in high category, 0.74. Keywords: Efektivitas, Cooperative Learning, NHT, Auditory Intellectually Repetition Abstrak. Penelitian ini bertujuan untuk mendeskripsikan efektivitas model kooperatif tipe NHT (Numbered Head Together) dengan Pendekatan Auditory Intellectually Repetition (AIR) dalam Pembelajaran Matematika. Jenis penelitian ini adalah penelitian pre-eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas X SMA Negeri 2 Bua Ponrang. Sampel penelitian adalah siswa kelas X1 yang terpilih melalui teknik random sampling. Data dikumpulkan menggunakan teknik tes dan pengamatan. Hasil penelitian menunjukkan bahwa (a) pembelajaran kooperatif tipe NHT dengan pendekatan Auditory Intellectually Repetition terlaksana dengan baik, (b) aktivitas siswa  berada dalam kategori ideal, (c) respons siswa terhadap pembelajaran cenderung positif, dan (d) hasil belajar siswa tuntas secara klasikal dengan gain ternormalisasi sebesar 0,74 yang berkategori tinggi.  Kata kunci: Efektivitas, pembelajaran kooperatif, NHT, Auditory Intellectually Repetition